Cloud computing strategy. (Chief Information Officer, Dept. of Defense, 2012)
The DoD cloud computing strategy has evolved to identify the most effective ways for the Department to capitalize on opportunities and take advantage of cloud computing benefits that accelerate IT delivery, efficiency, and innovation as an enterprise. The strategy has been expanded to address use of commercial cloud services in the Department's multi-provider enterprise cloud environment.